Association of osteoprotegerin with ascending aortic dissection. (25th November 2020) - Goliopoulou, A; Antonopoulos, A; Oikonomou, E; Miliou, A; Theofilis, P; Skotsimara, G; Mystakidi, V.C; Tousoulis, D
Abstract: Background: Thoracic aortic dissections are among the cardiovascular diseases with the highest mortality rates. Their often belated diagnosis and, hence, poor prognosis call for further research of their pathophysiology and possible biomarkers that will aid early diagnosis and increase survival rates. Osteoprotegerin is a known biomarker in cardiovascular disease, but it is yet to be determined whether it participates in aortic disease and thoracic aortic dissection in particular. Purpose: This clinical study aimed at researching the role of osteoprotegerin in thoracic aortic aneurysm and dissection. Methods: We compared three groups of patients; 20 patients with ascending aortic aneurysm (AAA), 10 patients with acute ascending aortic dissection (AAD) and 16 patients with normal aortic diameter undergoing cardiac surgery for other indication (control group). Serum samples were obtained from patients before surgery and osteoprotegerin levels were measured using the ELISA method. Results: One-way analysis of variance revealed a significant association between the examined groups of patients and levels of osteoprotegerin (AAD: 62.72±44.53 pmol/L, AAA: 33.43±8.08 pmol/L, Control: 48.61±29.47 pmol/L, p=0.03). Importantly, after post-hoc analysis osteoprotegerin levels were found to be increased in patients with AAD compared to patients with uncomplicated AAA (62.72±44.53 pmol/L vs 33.43±8.08 pmol/L, p=0.03) (Figure 1), whereas there was no statistically significant difference between patients with AAA and the control group (33.43±8.08 pmol/L vs 48.61±29.47 pmol/L, p=0.34). Conclusions: These findings suggest that osteoprotegerin may participate in the pathophysiology of aortic dissection but not in mechanisms of aortic dilatation. Therefore, detection of elevated osteoprotegerin levels in patients with diagnosed ascending aortic aneurysms might suggest an increased probability of dissection and, therefore, aid the decision-making process. Funding Acknowledgement: Type of funding source: None